MARINATED EFFECTS OF Etlingera elatior STEM FLOUR EXTRACT ON THE PHYSICAL AND ORGANOLEPTIC BROILER MEAT - P. I. S., RAHAYU; MIWADA, I. N. S.; OKARINI, I. A. (Majalah Ilmiah Peternakan; Vol 23 No 3 (2020): Vol. 23 No. 3 (2020)DO - 10.24843/MIP.2020.v23.i03.p04, 2020)
This study aims to determine the marinated effect of Etlingera elatior stem flour extract on the physical and organoleptic broiler meat. This study uses a completely randomized design (CRD) with four treatments and four replications. The four treatments are: broiler chicken meat marinated with kecombrang stem flour extract for 0 hours (P0), for 1 hour (P1), 3 hours (P2 ), and for 5 hours (P3). The variables observed were cooking loss, water holding capacity, pH, color and aroma. The results showed that the difference in the duration of marinated broiler chicken meat with kecombrang stem flour extract significantly (P<0.05) on cooking loss, pH, color and panelist preference value on the aroma, but no significant effect (P>0.05) on water holding capacity. The conclusion of this study was the treatment of 5 hours marination time with kecombrang stem flour extract 6% concentration, improved physical characteristics and subjective aroma of chicken meat filet which was good (cooking loss 38.09%, water holding capacity 63.23%, pH value 5, 17, subjective aroma with a score of 3.27 (like), brightness color (L’) 41.2, reddish color (a’) 6.07, and yellowish color (b’) 18.86.